Clinical care in craniofacial microsomia: A review of current management recommendations and opportunities to advance research. Issue 4 (16th October 2013) - Heike, C.L.; Hing, A.V.; Aspinall, C.A.; Bartlett, S.P.; Birgfeld, C.B.; Drake, A.F.; Pimenta, L.A.; Sie, K.C.; Urata, M.M.; Vivaldi, D.; Luquetti, D.V.; Cox, Timothy C.; et al.
Abstract Craniofacial microsomia (CFM) is a complex condition associated with microtia, mandibular hypoplasia, and preauricular tags. It is the second most common congenital facial condition treated in many craniofacial centers and requires longitudinal multidisciplinary patient care. The purpose of this article is to summarize current recommendations for clinical management and discuss opportunities to advance clinical research in CFM. © 2013 Wiley Periodicals, Inc.